Mucosal Inflammatory and Wound Healing Gene Programmes Reveal Targets for Stricturing Behaviour in Paediatric Crohn's Disease. (8th August 2020) - Haberman, Yael; Minar, Phillip; Karns, Rebekah; Dexheimer, Phillip J; Ghandikota, Sudhir; Tegge, Samuel; Shapiro, Daniel; Shuler, Brianne; Venkateswaran, Suresh; Braun, Tzipi; Ta, Allison; Walters, Thomas D; et al.
Abstract: Background and Aims: Ileal strictures are the major indication for resective surgery in Crohn's disease [CD]. We aimed to define ileal gene programmes present at diagnosis and linked with future stricturing behaviour during 5-year follow-up, and to identify potential small molecules to reverse these gene signatures. Methods: Antimicrobial serologies and pre-treatment ileal gene expression were assessed in a representative subset of 249 CD patients within the RISK multicentre paediatric CD inception cohort study, including 113 that are unique to this report. These data were used to define genes associated with stricturing behaviour and for model testing to predict stricturing behaviour. A bioinformatics approach to define small molecules which may reverse the stricturing gene signature was applied. Results: A total of 19 of the 249 patients developed isolated B2 stricturing behaviour during follow-up, while 218 remained B1 inflammatory. Using deeper RNA sequencing than in our previous report, we have now defined an inflammatory gene signature including an oncostatin M co-expression signature, tightly associated with extra-cellular matrix [ECM] gene expression, in those who developed stricturing complications. We further computationally prioritise small molecules targeting macrophage and fibroblast activation and angiogenesis which may reverse the stricturing gene signature. A model containing ASCA and CBir1 serologies and a refined eight ECM gene set was significantly associated with stricturing development by Year 5 after diagnosis AUC (area under the curve) (95th CI [confidence interval]) = 0.82 [0.7–0.94). Conclusions: An ileal gene programme for macrophage and fibroblast activation is linked to stricturing complications in treatment of naïve pediatric CD, and may inform novel small molecule therapeutic approaches.